Relationship between parental involvement and intrinsic motivation on learning Islamic education - Adamu, Zakiyu Ubale; Abdul Hakim, Abdullah; Tahir, Abdurrahman (2015)
Motivation is ann important element influencing learning and achievement. It is believed to affect human behaviour in a various situation like; learning, thinking, perceptions, creativity, and feelings. Many students cannot learn effectively as a result of not been stimulated. The present study aimed to identify a relationship between parental involvement (parenting, communicating, volunteering, learning at home, decision making and collaboration with the community) and students’ intrinsic motivation for learning Islamic education. The study used Quantitative approach; a survey type of descriptive study was employed. Two separate questionnaires were administered to a sample of 335 parents with their children attending the national religious secondary schools known as SMKA in Kuala Terengganu. The collected data was analysed using a statistical package for social science (SPSS) version 19. The finding shows a moderate positive relationship between parenting, communicating, volunteering, learning at home, decision making, collaboration with community and intrinsic motivation on learning Islamic education. Therefore, Schools should endeavour to plan tirelessly, so as to strengthen their commitment and enhance their relationship with parents as they are the co-partners in learning achievement of Islamic education.